Hearing Preservation in Stereotactic Radiosurgery for Vestibular Schwannoma - Tolisano, Anthony M.; Hunter, Jacob B. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Despite no universally accepted definition of hearing preservation following vestibular schwannoma (VS) treatment, numerous variables have been identified as possible factors that may affect hearing outcomes following radiotherapy. Age, pretreatment hearing, radiation dose, tumor location and size, length of follow-up, fractionation, and timing of radiation have all been explored, among other variables, as factors related to hearing outcomes following radiation. These variables and associated hearing outcomes will be explored in detail, summarizing the literature to date to improve patient counseling for those patients who present with serviceable hearing and are considering their VS management options.
Keywords: vestibular schwannoma; acoustic nerve; hearing; radiosurgery